Hemodynamic response to heated water immersion in older individuals with hypertension - Marçal, Isabela R. [UNESP]; Ngomane, Awassi Y. [UNESP]; Souza, Fernanda B. [UNESP]; Ciolac, Emmanuel Gomes [UNESP] (Wolters Kluwer, 2020)
The aim of this study was to evaluate blood pressure (BP), heart rate, arterial stiffness and endothelial reactivity responses to heated water immersion in older individuals with hypertension. Thirty-five sedentary individuals (67±5years) under treatment for hypertension were randomly assigned to water-based [n=20; 30min of seated resting in a heated swimming pool (30-32 ºC)] or land-based group [n=15; 30min of seated resting in a quiet room with controlled temperature (21-23 ºC)]. BP, heart rate, arterial stiffness and endothelial reactivity were measured before, immediately after (post) and 45min after (recovery) each session. Heart rate reduced (P<0.05) during the land-based session, and the reduction was maintained at post (~7bpm) and recovery (~9bpm), but no heart rate changes occurred during and after the water-based session. Systolic/diastolic BP increased (P=<0.001) at post (~29/10 mmHg) and recovery (~10/7 mmHg) in the water-based group, but not in the land-based group. No significant changes in pulse wave velocity and endothelial reactivity occurred in both groups. These results suggest that the hemodynamic response to heated water immersion should be taken into account when assessing the effect of heated water-based exercise on postexercise hypotension in older individuals with hypertension.
Keywords: Aging; Blood pressure; Hypertension; Immersion